Contraceptive options for HIV‐positive women: making evidence‐based, patient‐centred decisions. Issue 6 (17th February 2015) - Sharma, M; Walmsley, SL
<x xml:space="preserve">Abstract</x> Objectives Women of reproductive age represent a large proportion of the global population living with HIV/AIDS. With improvements in morbidity and mortality since the advent of combination antiretroviral therapy, contraception and pregnancy planning are an increasingly important issue for women living with HIV. This review aims to outline the key considerations when choosing contraceptive methods in HIV‐positive women and provides a review of the literature to inform decision‐making. Methods Pubmed was searched using the terms 'HIV', 'contraception', 'HIV progression', 'HIV acquisition', 'HIV transmission' and the combination of 'antiretroviral' and 'contraception'. Abstracts were reviewed and relevant articles were retrieved. Reference lists were also reviewed for pertinent citations. Results HIV and contraceptive methods can interact in several clinically meaningful ways. Concomitant use may result in altered contraceptive efficacy, drug−drug interactions, or increased toxicity. Hormonal contraceptives have not been shown to affect HIV progression. Notably, the impact of hormonal contraceptives on HIV transmission and acquisition remains unclear, particularly for injectable forms. Data are lacking on several newer methods of contraception including contraceptive rings, patches and intrauterine systems. Conclusions Effective, reliable contraception is important for HIV‐positive women. Efficacy, toxicity, drug interactions, and potential impacts on HIV disease progression, transmission, and acquisition must be assessed when making clinical decisions.